Phytochemistry and Potential of Sargassum binderi, Sargassum cinereum, Padina australis, and Turbinaria conoides as Medicinal Ingredients - Priamanatha , Dandy; Handayani, Sri; Zulfa, Astri (Universitas Nasional Jakarta, 2025)
This study investigated the phytochemicals and potential from macroalgae Sargassum binderi, Sargassum cinereum, Padina australis and Turbinaria conoides as material medicine. Samples in the study are taken from the sea around Kepulauan Seribu. Qualitative and quantitative tests conducted in the laboratory Nasional University Chemistry and Research Center Laboratory Plant Spices and Medicines. Research focuses on composition of phytochemicals consisting of groups of alkaloids, tannins, flavonoids, and saponins, then see its potential as a material drug through scientific studies. The results found in the research on every sample found contain all group phytochemicals in a way qualitative. Apart from that, levels of phytochemicals obtained are different. Sargassum binderies own high levels of flavonoids and saponins so that potential become drug as antioxidant, antiatherosclerotic, anti-inflammatory, antithrombogenic, antitumor, antiosteoporotic , antiviral, antibacterial, antifungal, and antiparasitic. While level tannin highest owned by Turbinaria conoides so that potential become material drug as antioxidant, antibacterial, antiviral, anticarcinogenic, anti-inflammatory, antiallergic, and vasodilator agents. Padina australis and Sargassum cinereum in a way sequentially own level highest from flavonoid and saponin groups, so that potential become material drug as antioxidant, antiatherosclerotic, anti-inflammatory, antithrombogenic, antitumor, antiosteoporotic, antiviral, antibacterial, antifungal, antiparasitic, and has hemolytic. All samples in a way qualitative contain alkaloids, so that has the potential to also become a material drug as anticancer, antibacterial, antiviral, antifungal, cytotoxic to herbivorous, analgesic, and relaxant muscle. Research more carry on about activity pharmacology, compounds phytochemicals specific, alkaloid levels, and dosage best can open knowledge about material drug from more macroalgae complete